Effect of Surfactant Addition on the Dispersion and Antioxidant Performance of Pyrogallol in Biodiesel - Yusri, Silvya; Nasikin, Mohammad; Sutanto, Hery (Makara Journal of Science, 2020)
Biodiesel is one of the most feasible energy sources that can be used as a replacement for fossil fuel. Biodiesel has several advantages over conventional fuels because of its availability, renewability, and high combustion efficiency. However, biodiesel that contains unsaturated fatty acid methyl esters is prone to oxidation during the blending process and storage period. The complete oxidation reaction of biodiesel produces insoluble gums that could potentially plug the fuel engines. This reaction has become the main barrier for biodiesel to compete with other biofuels. Among several methods, the addition of antioxidants is the most cost-effective method to prevent the oxidation reaction in biodiesel. Pyrogallol (PY), which is one of the best antioxidant additives for biodiesel, was used in this research to evaluate its performance. However, the fact that PY is partially soluble in biodiesel is considered a problem in the application of PY as an antioxidant additive in biodiesel. In this research, three different surfactants were added to increase the dispersion and performance of PY in biodiesel. Dispersion test, acid number analysis, and iodine value analysis were performed to evaluate the effect of surfactant addition on the dispersion and antioxidant performance of PY in biodiesel. The surfactant glycerol monostearate showed the best result in increasing the dispersion of PY in biodiesel compared with sorbitan monooleate and polyglyceryl-4-isostearate (PG4IS). By contrast, the best performance of PY in preventing the oxidation of biodiesel was achieved with the addition of PG4IS.